COMPARISON OF INFRARED AND OPTOCOUPLER SENSORS PERFORMANCE FOR LAB-SCALE RPM MEASUREMENT SYSTEM - Afifah Amatullah, Elin Nur; Ekawita, Riska; Yuliza, Elfi (Indonesian Physical Review, 2022)
In utilizing various alternative energy, generators are used to convert alternative energy into electrical energy, for example, biomass, wind, and hydroelectricity. Generally, the measurements made on the generators are rotational speed measurements in the form of revolutions per minute (RPM). In developing lab-scale alternative power sources, the availability of generators with complete quality and specifications is still minimal, including RPM capacity. Therefore, the measurement which can read the RPM accurately, digitally, and automatically is needed. However, the measurement tools available are still manual, not automatic, and prone to parallax errors. Hence, a digital and automatic RPM measurement was developed in this study. Two different sensors were used to develop digital RPM based on a microcontroller. The stages obtained started with electronic system development, calibration, and testing of lab-scale renewable energy systems. The measurement can be read from the infrared and optocoupler sensors on the Archimedes turbine. The measurement results showed that the use of the Optocoupler sensor is more accurate than the infrared sensor. This is based on the data obtained from calibration and testing results on the Archimedes turbine. This RPM measurement is digital and real-time.